Living Qur’an di Kalangan Mahasiswi: Studi Kasus di Asrama Pemerintah Aceh Pocut Baren Sleman Yogyakarta - Nurhalizha, Iin; Baroroh, R. Umi (JOIES (Journal of Islamic Education Studies), 2017)
This article aims to examine the verses that have grown and developed among female students who live in the Government of the Aceh Pocut Baren Sleman Yogyakarta. The formulation of the problem in this research is how the efforts of female students to make verses of the Qur'an 'live' in daily life and how the responses of students are related to activities that reflect the activities of everyday life of the Qur'an at the Aceh Pocut Baren Government Dormitory in Sleman Yogyakarta. Research uses a qualitative approach. Research Methodology; Living Qur’an with the background of activities is the application of activities that reflect the everyday life of the Qur’an activities in the Government of Aceh Pocut Baren Sleman Yogyakarta. Sources of data obtained are, through interviews, observations, and documentation. The results of this study indicate that the efforts of female students in making the verses of the 'life' are carried out by implementing activities that reflect the activities of everyday life of the Qur'an at the Aceh Pocut Baren Government Dormitory Sleman Yogyakarta. Furthermore, the students' response to the activity, which can foster student love for the Qur'an, can be seen from the habituation and practice of reading verses to memorization and implementation in daily activities.